The interplay between bystander cardiopulmonary resuscitation and ambient temperature on neurological outcome after cardiac arrest: A nationwide observational cohort study. (July 2021) - Hayashida, Kei; Takegawa, Ryosuke; Nishikimi, Mitsuaki; Aoki, Tomoaki; Emoto, Ryo; Shinozaki, Koichiro; Miyara, Santiago J.; Rolston, Daniel M.; Li, Timmy; Shoaib, Muhammad; Fukuda, Tatsuma; Molmenti, Ernesto P.; et al.
Abstract: Background: At lower ambient temperature, patients with out-of-hospital cardiac arrest (OHCA) easily experience hypothermia. Hypothermia has shown to improve the rate of successful return of spontaneous circulation (ROSC) in animal models. We hypothesized that lower temperature affects the impact of bystander cardiopulmonary resuscitation (CPR) on the increased odds of a favorable neurological outcome post-OHCA. Methods: This study used information collected by the prospective, nationwide, Utstein registry to examine data from 352, 689 adult patients who experienced OHCA from 2012 to 2016 in Japan. The primary outcome was a 1-month favorable neurological outcomes. Multivariable logistic regression analyses were conducted to test the impact of bystander CPR according to the temperature on the favorable outcome. Results: A total of 201, 111 patients with OHCA were included in the complete case analysis. The lower temperature group had lower proportions of receiving bystander CPR (46.5 vs. 47.9%) and having favorable outcome (2.1 vs 2.8%) than those in the higher group. Multivariable analysis revealed that bystander CPR at lower temperatures was significantly associated with favorable outcomes (adjusted odds ratio, 1.22; 95% CI, 1.09–1.37), whereas bystander CPR at higher temperatures was not associated with favorable outcomes (1.02; 0.92–1.13). The nonlinear relationship using a spline curve in the multivariable model revealed that odds ratio of favorable neurological outcomes associated with bystander CPR increased as the temperature decreased. Conclusion: Bystander CPR was associated with favorable neurological outcomes at lower temperatures. The odds of a favorable outcome associated with bystander CPR increased as the temperature decreased.